Some new theoretical issues in systems thinking relevant for modelling corporate learning - Minati, Gianfranco (The learning organization, 2007)
Purpose - The purpose of this paper is to describe fundamental concepts and theoretical challenges with regard to systems, and to build on these in proposing new theoretical frameworks relevant to learning, for example in so-called learning organizations.Design methodology approach - The paper focuses on some crucial fundamental aspects introduced in the literature in order to establish a general rather than generic usage of the systems concept. Issues of definition and theoretical frameworks are clarified before introducing new theoretical challenges for Systems Thinking, such as the perspective of a General Theory of Emergence (GTE), new modelling approaches and new concepts including Multiple Systems (MSs) and Collective Beings (CBs).Findings - New approaches for modelling management and corporate learning are described. The paper also explains the Dynamical Usage of Models (DYSAM) developed to deal with MSs and CBs for managing learning systems able to self-design evolutionary strategies.Originality value - The paper expands understanding of the notion of system and underlines the relevance of systems thinking in modelling and facilitating corporate learning.